Self-Management for People with Inflammatory Bowel Disease. (2008) - Saibil, Fred; Lai, Emily; Hayward, Andrew; Yip, Jeanne; Gilbert, Cameron
Abstract : In North America and the United Kingdom, we are in the age of self-management. Many patients with chronic diseases are ready to participate in the therapeutic decision-making process, and join their physicians in a co-management model. It is particularly useful to consider this concept at a time when physician shortages and waiting times are on the front page every day, with no immediate prospect of relief. Conditions such as diabetes, asthma, chronic obstructive pulmonary disease, recurrent urinary tract infections and others lend themselves to this paradigm of medical care for the informed patient. The present paper reviews some of the literature on self-management for the patient with inflammatory bowel disease (IBD), and provides a framework for the use of self-management in the IBD population, with emphasis on the concept of a patient passport, and the use of e-mail, supported by an e-mail contract, as proposed by the Canadian Medical Protective Association. Examples of specific management strategies are provided for several different IBD scenarios. Eliminating the need for some office visits has clear environmental and economical benefits. Potential negative consequences of this form of patient care are also discussed.